Electro-hydro-mechanical braking system for passenger vehicle - Rahman, Mohammed Ataur; Amsyar, Mohamad; Ihsan, Sany Izan; Mohiuddin, A. K. M. (Science Alert, 2018)
Background and Objective: Deceleration or stopping the vehicle without a diving and lateral acceleration is essential to develop an effective braking system. The antilock braking system (ABS) and electronic stability control (ESC) has been introduced to improve the braking performance of the vehicle. However, due to the insufficient human effort, the ABS and ESC to some extent, not function well. This study develops an electro-hydro-mechanical braking system by associating the wheel speed sensor and accelerator sensor. It had been developed the additional actuation force on the brake pad to decelerate the vehicle instantaneously in the desired braking distance corresponding to the speed with less lateral acceleration. Materials and Methods: This study investigates the DC motor amplified braking system theoretically by solid work simulation model and experimentally by developing an intelligent system for controlling the DC motor based on the Markov Decision Process model. Results: The simulation model has shown that a full load passenger car needs 15.7 Mpa of braking pressure to stop 50 km/h vehicle in 10 m. The experimental results of the model show that the pressure develops when the pedal fully applied without and with aids of the DC motor is 910 kPa and 1130kPa, respectively, which contribute to increase pressure about 23.3%. Conclusion: The effectiveness of the DC motor amplified braking system would be able to break the vehicle to decelerate as soon as release the brake pedal even without the driver action which might prevent the fatal accident on the road.